Effect Of Intermediate Rolling On The Transport Properties Of Ag-Sheathed (Bi,Pb)2Sr2Ca2Cu3Ox Superconductor Tapes - Abd Shukor, Roslan; Chen, Soo Kien; Lau, Kok Tee (IOP Publishing Ltd., 2002)
We have studied the transport properties of Ag-sheathed (Bi,Pb)2Sr2Ca2Cu3Ox (Bi-2223/Ag) superconductor tapes prepared by different thermo-mechanical treatments from the aspects of structural quality and the intermediate rolling effect. Intermediate rolling improved the self-field Jc of the tapes by a factor of three compared to tapes without intermediate rolling. A similar behaviour of Jc decreasing in the magnetic field was observed for all samples. It is suggested that weak and strong links play a role in the decrease. The contribution of strong links in all tapes is calculated and is briefly discussed. The pinning behaviour of the tapes in the applied field is discussed, and the critical magnetic fields at which the pinning force density vanished were found to be from 0.25 to 0.77 T. Intermediate rolling was found to improve the structural quality of the tapes.